2008
DOI: 10.3390/ijerph6010051
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Economic Evaluations of Tobacco Control Programs

Abstract: Each year, an estimated 443,000 people die of smoking-related diseases in the United States. Cigarette smoking results in more than $193 billion in medical costs and productivity losses annually. In an effort to reduce this burden, many states, the federal government, and several national organizations fund tobacco control programs and policies. For this report we reviewed existing literature on economic evaluations of tobacco control interventions. We found that smoking cessation therapies, including nicotine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
60
1
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(63 citation statements)
references
References 62 publications
1
60
1
1
Order By: Relevance
“…Government initiatives that have reduced tobacco consumption, including educational campaigns, limiting smoking in public places, and higher cigarette taxes, have been an extremely cost-effective way to reduce cardiovascular disease. 15 Heart institutes should lobby for legislation that improves cardiovascular health across the whole population, including everything from better labelling of food products to more bicycle paths. It could be argued that such an approach goes far beyond our obligation as physicians; however, we should be advocates for our patients, present and future, and preventing cardiovascular events is so much better than treating them.…”
Section: Future Role Of Heart Institutes: Local and National Opportunmentioning
confidence: 99%
“…Government initiatives that have reduced tobacco consumption, including educational campaigns, limiting smoking in public places, and higher cigarette taxes, have been an extremely cost-effective way to reduce cardiovascular disease. 15 Heart institutes should lobby for legislation that improves cardiovascular health across the whole population, including everything from better labelling of food products to more bicycle paths. It could be argued that such an approach goes far beyond our obligation as physicians; however, we should be advocates for our patients, present and future, and preventing cardiovascular events is so much better than treating them.…”
Section: Future Role Of Heart Institutes: Local and National Opportunmentioning
confidence: 99%
“…Examples: tobacco tax raises 1,6 ; mass media campaigns; expansion of quitline use; provision of nicotine replacement products for quitting smoking. Australian researchers found that a national tobacco campaign would be cost-saving.…”
Section: Tobacco Usementioning
confidence: 99%
“…Economic evaluations of tobacco control policies typically account for the loss of quality of life associated with suffering these diseases by means of health related quality of life (HRQoL) indices that permit the calculation of some outcome measure of life years adjusted by quality. Among such measures, the Quality Adjusted Life Year (QALY) [4,5,21] assigns a value of one to one year of life lived full health and zero to death. A relevant research question, with important implications for policy, is whether smoking affects HRQoL over and above its effect on the likelihood of contracting disease.…”
Section: Introductionmentioning
confidence: 99%
“…For each of these dimensions respondents can report five levels of severity (no problems/slight problems/moderate problems/severe problems/extreme problems). The resulting 5 5 potential states are mapped into a one dimensional index, known as the EQ-5D-5L "score" or "tariff", usually ranging between unity (representing the best possible outcome of "no problems" in all five dimensions) and zero (worst possible outcome) [22].…”
Section: Introductionmentioning
confidence: 99%